TRAINING AND SOCIALISATION OF INCLUSIVE EDUCATION OF STUDENTS BY MEANS OF ADAPTIVE ROCK CLIMBING - Зюзь, Володимир (SWorldJournal, 2025)
The article is devoted to the issues of rehabilitation and organization of inclusive education of students with special educational needs at PSTU in the conditions of functioning of higher professional education.Inclusive (adaptive) education in physical